Formulasi Nasal Spray Anti-Influenza yang Mengandung Nanopartikel Perak : Nasal Spray Anti-Influenza Nanopartikel Perak - Sutriyo; Wilbert Wylie; Kurnia Sari Setio Putri; Okti Nadia Poetri; Rahmasari, Ratika (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2021)
Influenza A virus is one of the most common causes of respiratory disease in the world. Even though, vaccines and anti-influenza virus are become the first line for therapy, but the mutation ability of influenza virus is able to cause several outbreaks in the world. Silver nanoparticles (AgNP) have been proven to exhibit antiviral activity; however, the use of AgNP in pharmaceutical products is still limited. In this study, we aimed to formulate nasal spray containing AgNP, to evaluate its physicochemical properties, and its antiviral activity toward H5N1 influenza A virus. AgNP were synthesized using chemical reduction method with polyvinyl alcohol as stabilizer, and further prepared into nasal spray product. Physicochemical properties and anti-hemagglutination activity of nasal spray were further evaluated. The nasal spray contained different size of AgNP (less and more than 50 nm) showed physical stability after 28 days storage. However, Anti-influenza evaluation of nasal spray contained AgNP less than 50 nm exhibited better anti-hemagglutination activity against influenza A virus.